Penggunaan Media Pohon Pintar Angka untuk Mengembangkan Kemampuan Membilang bagi Anak Usia Dini - Azizah, Suci Midsayhri; Wahyuni, Fitri; Muneng, Nadya Lutfiya (Absorbent Mind, 2023)
This article aims to describe the ability to count numbers for group B students in the Harapan Bunda PKK Playgroup and to describe the use of numerical innovative tree media to develop the ability to calculate numbers for group B students in the Harapan Bunda PKK Playgroup. This research uses a descriptive qualitative research method and data collection procedures through interview techniques, observation, and documentation. The collected data related to students' numeracy skills and the use of innovative tree media were analyzed using data reduction, data presentation, and conclusions. Based on the results of the data analysis, it was concluded that the ability to count the numbers of group B students in the Play Group PKK Harapan Bunda Muneng Balong Ponorogo can be said to be better because the children's abilities are better than before. The use of innovative tree media has proven to be more capable of developing the ability to count numbers for group B students in the PKK Harapan Bunda Play Group, Muneng, Balong, and Ponorogo.